O gerenciamento das unidades básicas de saúde do município de Bauru : dificuldades e facilidades - Cardoso, Solange Nardo Marques (2007)
The city of Bauru was a groundbreaker in implementing the local health system, anticipating the very 1988 Federal Constitution which established SUS basic principles. However, both the groundbreaking and the development of health municipalization did not guarantee the city the necessary investments or prioritization of the basic attention. The years that followed showed an inversion of the health system model which privileged remedial actions rather than health prevention and promotion actions. This study s general objective was to characterize the UBS (Health Basic Units) of the Health Department of the city of Bauru and delineate a panorama of their production and of their managers actions. The specific objectives were to identify the professional profile of the UBS managers; to point out the facilitative aspects and difficulties found by managers to deal with human, financial, material and maintenance, and physical-structural resources, as well as to deal with the UBS s work processes, with the social control and the relationship with the Health City Department. The methodology adopted was the exploratory and descriptive research. A questionnaire was used to data collection, aiming at characterizing the managers profile and pointing out easy and difficult aspects of the management. Results showed predominance of females and of nursing professionals. Only a small part of the professionals (18,75%) is specialized in the area of public health and 50% hold a management course. All managers perform management and assistance activities, with commitment in terms of the latter because of the excessive bureaucracy and lack of human resources. Many difficulties were pointed by the managers; however, the main problem appears to be the deficit of human resources. Another difficulty that deserves to be highlighted was the lack of acceptance, support, and participation of the managers in actions planning, that is, in the decision taking process of the SMS (Health City Department). The consequences of the lack of investment and of prioritization of the basic attention in the city of Bauru lead to the deterioration of the health system services as well as to the human resources deficit, among others. Within such context, the managers face huge difficulties in UBS management. The manager s role is fundamental in the process of change in order to invert the present assistance model, and also to search for improvement in the quality of assistance offered to the population in consonance with SUS principles.